PUSAT STUDI LEMBAGA PEMASYARAKATAN FAKULTAS HUKUM UKI - Petrus Irwan Panjaitan (to-ra, 2019)
Abstract Pusat Studi Lembaga Pemasyarakatan is an institution that conducts scienti c analysis of the correctional system; inmate behavior; of cer behavior; coaches behavior; the regulations that apply in Corrections Institutions; facilities available to the public’s view of the Penitentiary; in addition there are also problems that occur in the Penitentiary; such as a criminal period that is too short; community prisoners’ social relations; the problem of assimilation into and outside the institution and the problem of the prisoner’s biological needs; can be analyzed or studied in more depth; to make effective analysis of the existence of Correctional Institutions requires an academic authority through the Higher Education Law Institution as a Higher Education Institution, the UKI Faculty of Law should properly have a Correctional Institution Study Center when entering the age of 40 years as well as maintaining the best predicate among the Law Pakuitas as a consideration of establishment Study Centers that until now there has not been a Faculty of Law that has such Study Centers; Penitentiary a strategic part of the criminal justice system; Penal Institutions need to be empowered in their role in society. Keywords: Lembaga Pemasyarakatan; prison; study center; criminal justice system.